Epicurus and B. F. Skinner: In search of the good life. Issue 1 (25th November 2016) - Neuringer, Allen; Englert, Walter
Abstract : This paper examines similarities in the works of Epicurus, an ancient Greek philosopher, and B. F. Skinner, a behavioral psychologist. They both were empiricists who argued in favor of the lawfulness of behavior while maintaining that random events were included within those laws. They both devoted much effort to describing how individuals could live effective, rewarding and pleasurable lives. They both emphasized simple and natural pleasures (or reinforcers) and the importance of combining personal pleasures with actions that benefit friends and community. They both opposed punishment and all aversive measures used by governments and religions to control behaviors. And both created utopias: a real community, The Garden, where Epicurus lived with his followers, and a fictional one, Walden Two, by Skinner. We consider how a combination of the ideas of Epicurus and Skinner can contribute to their common goal of helping people to live better lives.